Pengenalan Teknologi Robotik dalam Optimalisasi Logistik dan Distribusi Rantai Pasok untuk Siswa SMK - Bonitasari Nurul Alfa; Adizty Suparno; Ketty Siti Salamah (CV. IRA PUBLISHING, 2026)
The rapid advancement of technology in the Industry 4.0 era requires a workforce proficient in automation, including robotics, for logistics and distribution systems. However, many vocational high school students still lack access to and understanding of such technologies. This community service program was conducted at SMKS 10 November Jakarta to introduce robotics technology in the context of logistics and distribution. The activity consisted of three main stages: an introduction to basic robotics and supply chain principles; hands-on simulation with mini robots; and student-led development and presentation of robot prototypes. The program used a participatory, practical approach, involving teachers in supporting technology-based learning. Results showed high student enthusiasm and positive feedback from the school, highlighting the activity’s relevance in strengthening vocational technology skills. Program outputs include a video documentation, student-built robot prototypes, and a draft scientific article. This initiative is expected to enhance students’ understanding of modern logistics technology and foster ongoing collaboration between universities and vocational schools to better prepare graduates for the automation-driven industrial world.